Effectiveness of Applying the GASING Method in Multiplication of Two-Digit Numbers in Elementary Schools - Yuliani, Ni Putu; Antari, Ni Wayan Astri; Wulandari, Putu Sintya; Saspanya, Kadek Darma; Prayoga, I Wayan Eka Agus; Yasa, I Made Bayu Putra; Werang, Basilius Redan (PT FORMOSA CENDEKIA GLOBAL, 2024)
Understanding the concept of multiplying two numbers in mathematics learning is something that should be taught to students as a basis for understanding more complex mathematical operations. This research aims to analyze the effectiveness of mathematics learning using the GASING method on multiplication of two-digit numbers. This research uses a type of library research. Data collection uses documentation techniques. Next, the data was analyzed using content analysis techniques. This analysis is used to obtain valid references. The research results show that the GASING method can deepen the concept of multiplication packaged with interesting and fun games which have an impact on increasing academic grades. Thus, the application of the GASING method in learning has implications for the active involvement of students in the classroom which has an impact on strengthening in-depth understanding of mathematical concepts.